The effect of the one-minute paper strategy on achievement and innovative thinking when teaching sociology for fourth grade literary students (Journal of the College of Basic Education, 2022)
Objective of the research: The researcher formulated the following two zero hypotheses:1- There is no difference with a score at the level of 0.05 between the arithmetic mean of the achievement scores of the group students and the arithmetic mean of the achievement scores of the control group students in the achievement test.2- There is no statistically significant difference at the level of 0.05 between the arithmetic mean scores of the experimental group students and the arithmetic mean scores of the control group students in the innovative thinking test.